(untitled) (Jurnal Ilmu Komunikasi, 2025)
This study aims to understand how the families of employees at PT. Traktor Nusantara construct the meaning of their culture shock experiences during relocations to different regions. Using a qualitative approach and phenomenology of communication, the research explores family communication dynamics, emotional support, and adaptation strategies. Data were collected through in-depth interviews, observations, and documentation involving four main informants who are employees and several family members of PT. Traktor Nusantara. The findings indicate that the culture shock experiences of families are influenced by internal factors such as adaptability and emotional support, as well as external factors like language, cultural, and social norm differences. Open communication within the family is key to overcoming these challenges. Additionally, adaptation strategies include building relationships with local communities and embracing new cultures as learning opportunities. This study confirms that the construction of the meaning of culture shock within employee families is a result of dynamic social interactions. These findings align with Berger and Luckmann's social construction theory, which emphasizes that meaning is formed through the processes of internalization, objectification, and externalization. The study also provides recommendations for companies to develop support programs, such as cultural adaptation training and counseling services, to enhance the well-being of employees and their families.